Implementasi Komunikasi Guru dalam Mengajar pada Anak Tunanetra - Belya Nadine Islamiyah Legiana; Nina Yuliana (Pusat Riset dan Inovasi Nasional, 2023)
An abstranct is a brief summary of a research article, thesis, review, conference proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript orEngaging in communication within the realm of teaching and learning is fundamentally a social activity. It becomes particularly crucial for educators when guiding visually impaired students, necessitating the utilization of a variety of learning strategies that extend beyond the confines of sight within the classroom. To effectively achieve educational goals, teachers employ a myriad of methods to convey instructional materials. This research endeavors to scrutinize the communication strategies implemented by teachers while educating visually impaired children, delving into the intricate communication dynamics between educators and students. The study delves into the exploration of multimodal learning techniques employed by teachers to impart educational messages within the classroom setting. The results elucidate distinct phases within the learning strategies embraced by teachers, ranging from the cultivation of personal and intimate connections to the meticulous selection of teaching materials. The study sheds light on the application of multi-modal learning, encompassing auditory-kinesthetic, kinesthetic-visual, and audio-visual styles. Additionally, the research delineates stages pertaining to learning outcomes and the responses of teachers to their students.